A methodology to assess energy-demand savings and cost-effectiveness of adaptation measures in educational buildings in the warm Mediterranean region. (November 2022) - Heracleous, C.; Michael, A.; Savvides, A.; Hayles, C.
Abstract: Educational building stock in Cyprus are a significant part of the public building stock, with these buildings leaning towards being less energy-efficient, especially in comparison to other public buildings. The energy and climate directives set by the European Union for 2050 call for changes in the building sector, particularly for existing public building stock. This study suggests a design approach and assessment for retrofitting scenarios, which meet energy demands for educational buildings in Cyprus, based on their long-term cost effectiveness. Adaptation measures refer to changes in the geometry, construction, and operation of buildings. The approach combines energy demand modelling through dynamic software simulation using Integrated Environmental Solutions (IES-VE) and retrofit options, ranked by life cycle costing analysis (LCCA). These options may have very different upfront costs, but also very different carbon implications, and they result in different life expectancy predictions. The research findings contributes to delivering novel knowledge in the rather limited literature regarding the implication of adaptation measures on energy performance of educational buildings in the Mediterranean region and especially in correlation to their life-cycle cost. The aim is to give the stakeholders as much information as possible regarding their interventions, so that they can make informed decisions. This information will then be used to develop a framework that may be used more extensively to support decision-making in retrofitting existing educational buildings for climate change resilience. Highlights: LCCA of retrofit approaches was conducted in schools of Southern Europe. Energy ranking of retrofit approaches was based on dynamic software simulation. Retrofit approaches reduce energy demand by 69% without particular changes to LCCA. The study is a trustworthy tool for decision-making in energy retrofitting projects. The selection of input parameters for LCCA is highly influential.